Pengaruh Ekstrak Daun Pedada (Sonneratia caseolaris) Sebagai Antihiperkolesterolmia Pada Mencit (Mus musculus) - Ramlah, Ramlah (bionature, 2018)
Abstract. This study was conducted to determine the effect of extract leaf pedada (Sonneratia caseolaris) to total cholesterol levels of mice (Mus musculus) male ICR strain. Leaf pedada extracted using 96% methanol by maceration. This study is a completely randomized design (CRD), which consists of 5 treatments and 5 replicates the normal group (distilled water), positive group (Simvastatin), a group of leaf pedada extract at a dose of 125, 250 and 500 mg / kg. The extract was dissolved using Carboxy Methyl Cellulose (CMC) 0.5% and given orally in mice which had previously been given a high cholesterol feed. The results showed the methanol extract of leaves cemba with the dose of 500 mg/kg hads the highest effectiveness in lowering total cholesterol levels in mice which have hypercholesterolemia with a 30,20 % percentage drop. These results indicate that of the giving leaf extract pedada (Sonneratia caseolaris) able to lower total cholesterol levels of mice (Mus musculus) male hypercholesterolaemia.Keywords: Antihipercholesterolemia, total cholesterol, Methanol extract ofÂ  leaf pedada (Sonneratia caseolaris), mice (Mus musculus) ICR male.